Penguatan Kesehatan Dan Ekonomi Kreatif Melalui Pemanfaatan Limbah Minyak Jelantah Menjadi Komoditas Jual Sabun Cuci Siap Pakai Di Desa Panti - Wijaya, Jannitra Aryo; Theodorus Dani Darmawan; Elita Maulidya Naura; Hilwa Asy Syifa Aulia; Diva Marta Dwijayanti; Zahniar; Mohammad Ralief Yusrial Fabiyyanza; Achmad Faza Abdillah; Fahriza Adi Pramudya; Tsabita Nafisa (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Hypertension is a serious health issue in Panti Village, Jember Regency, caused by the local community's low knowledge about hypertension prevention and the use of used cooking oil in cooking. Using waste cooking oil can be a risk factor for hypertension and environmental pollution. That waste cooking oil can be processed into laundry soap as an alternative solution. This community service program focuses on empowering the PKK community in Panti Village through training on processing waste cooking oil into laundry soap to increase knowledge about hypertension prevention and provide new economic potential. We hope this program can reduce hypertension rates and improve the economic welfare of the Panti Village community.